2023
DOI: 10.1002/clc.24137
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of catheter ablation of atrial fibrillation in the very elderly (≥80 years old): Insights from the UC San Diego AF Ablation Registry

Omar M. Aldaas,
Douglas Darden,
Praneet S. Mylavarapu
et al.

Abstract: BackgroundCatheter ablation improves outcomes in symptomatic atrial fibrillation (AF) patients. However, its safety and efficacy in the very elderly (≥80 years old) is not well described.HypothesisAblation of AF in the very elderly is safe and effective.MethodsWe performed a retrospective study of all patients who underwent catheter ablation enrolled in the University of California, San Diego AF Ablation Registry. The primary outcome was freedom from atrial arrhythmias on or off antiarrhythmic drugs (AADs).Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We thank Kataoka et al for their comments regarding our recently published article on catheter ablation of atrial fibrillation in very elderly patients (≥80 years old) 1 . While the unadjusted time‐to‐event analysis may be more reflective of real‐world clinical practice, we adjusted for multiple potential confounders to more clearly assess the association of catheter ablation with all‐cause hospitalizations and mortality in the very elderly.…”
mentioning
confidence: 99%
“…We thank Kataoka et al for their comments regarding our recently published article on catheter ablation of atrial fibrillation in very elderly patients (≥80 years old) 1 . While the unadjusted time‐to‐event analysis may be more reflective of real‐world clinical practice, we adjusted for multiple potential confounders to more clearly assess the association of catheter ablation with all‐cause hospitalizations and mortality in the very elderly.…”
mentioning
confidence: 99%
“…Aldaas and colleagues demonstrated that catheter ablation for atrial fibrillation was similarly effective and feasible in patients aged 80 years or older when compared with a younger cohort. 1 Several concerns have been raised.…”
mentioning
confidence: 99%
“…Elderly patients had a significantly higher cumulative incidence of all‐cause death/hospitalization after catheter ablation in their unadjusted comparative analyses. 1 This is not surprising as elderly patients have multiple comorbidities and more advanced sarcopenia than the younger cohort. These worse baseline characteristics may have a negative prognostic impact, regardless of the correction of atrial fibrillation.…”
mentioning
confidence: 99%
See 2 more Smart Citations